Municipal social services in the prevention of women’s homelessness - Sánchez Castiñeira, Sergio; Sales, Albert; Ayguasenosa Soro, Noemí (Cuadernos de Trabajo Social, 2025)
This research aims to analyse the preventive role of primary social services against female homelessness through the analysis of semi-structured interviews with women living rough or staying in night shelters (22) and with social workers from non-government associations (7). The results show that gender-based violence, mental illness, childhood abuse, institutionalisation in juvenile or rehabilitation centres, or a conflictive relationship with child protection services represent high risk factors for women roofless. However, these problems tend to be presented in a disconnected way through the categorisations of professionals, the relationships that social services establish and the benefits and services available. The research also points that an institutional framework of scarce and inadequate resources, in an ideological context of individual accountability and patriarchy, may favour oppressive interventions and the re-victimisation of homeless women. In conclusion, public local social services must be organised to be more attentive to the multiple causes and manifestations of female homelessness. Social workers must be able to provide personalised and sufficient support. In addition, professionals should coordinate the different services at the local level to improve the comprehensiveness of the intervention (housing, employment, health and work-life balance). Finally, organisations must generate spaces for critical reflection and participation so as not to reproduce excluding and oppressive attitudes.